2017
DOI: 10.1111/apa.13695
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac patients detected during type 1 diabetes surveillance had similar issues to those diagnosed on a clinical basis

Abstract: Aim: Screening children with type 1 diabetes for coeliac disease is controversial, because they often appear asymptomatic. Our aim was to establish whether active screening should be recommended.Methods: This study focused on 22 children whose coeliac disease was detected by serological screening during diabetes surveillance and 498 children diagnosed because of a clinical suspicion. We compared the clinical and histological data at diagnosis and the children's adherence and responses to a gluten-free diet. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
11
0
3
Order By: Relevance
“…Se observó una asociación en la DM-I, tiroiditis autoinmune, síndromes de Down, Turner y Williams, déficit selectivo de IgA, alergia al polen, EII, epilepsia y familiares de primer grado. La prevalencia de enfermedades asociadas incrementa con la edad 33,34,36,37 .…”
Section: Síntomas Típicosunclassified
See 2 more Smart Citations
“…Se observó una asociación en la DM-I, tiroiditis autoinmune, síndromes de Down, Turner y Williams, déficit selectivo de IgA, alergia al polen, EII, epilepsia y familiares de primer grado. La prevalencia de enfermedades asociadas incrementa con la edad 33,34,36,37 .…”
Section: Síntomas Típicosunclassified
“…El grado de atrofia vellositaria moderado-severo (Marsh III) es el más prevalente en niños y niñas, y se correlaciona con el nivel de anticuerpos ATG IgA 37,40 . Es necesario realizar un cribado serológico de celiaquía en pacientes con DM-I, a pesar de no mostrar una clínica exacerbada, porque se ha observado que al menos la mitad de los niños y niñas con DM-I en el momento del diagnóstico de la EC ya presentan atrofia vellositaria subtotal o total.…”
Section: Síntomas Típicosunclassified
See 1 more Smart Citation
“…In this issue of Acta Paediatrica, Laitinen et al (1) explore symptoms and mucosal damage in 22 patients with type 1 diabetes who were screened for coeliac disease and compared them to 498 individuals diagnosed with coeliac disease on a clinical basis. The authors concluded that screening for coeliac disease should be considered among children with type 1 diabetes, which is in line with current recommendations (2)(3)(4).…”
Section: Screening For Coeliac Disease In Type 1 Diabetesmentioning
confidence: 99%
“…We should consider that it may not be entirely accurate to assume that most children and teenagers with T1DM and celiac disease have no or minimal symptoms: in fact, they may well have mild or under-reported symptoms, not unlike those of patients with celiac disease alone. 20 Additionally, a GFD does not seem to negatively influence the quality of life and may be beneficial to patients with T1DM and celiac disease, regardless of symptoms. 21 A study in a large series of such patients showed that those who achieved normalization of their TTG titers had better control of their glycated hemoglobin and growth.…”
mentioning
confidence: 99%